Development of solid rocket propulsion system at UTM - Mohd. Jaafar, Mohammad Nazri; Wan Ali, Wan Khairuddin; Dahalan, Md. Nizam; Mamat, Rizalman (Faculty of Mechanical Engineering, Universiti Teknologi Malaysia, 2004)
Rockets have been used from as early as the thirteenth century as fireworks and weapons. However, since then the usage of rockets have been diversified. Nowadays, rockets are used from as small as model rocketry for hobbyist to as large as a satellite launcher. Another diversified usages of rockets is as a launch vehicle for cloud seeding. In line with this, over the past decade Universiti Teknologi Malaysia (UTM) has been developing capabilities to launch a small rocket. Due to the low cost of raw materials and ease of production process, composite propellant is the best choice for this purpose. Potassium nitrate based solid propellant has been investigated in order to study their properties and performance. As a result, it is found that this propellant is capable of reaching the necessary range for cloud seeding (6 km - 7 km).